NOTA and NODAGA Radionuclide Complexing Agents: Versatile Approaches for Advancements in Radiochemistry - Claudia G. Chambers; Jing Wang; Tamer M. Sakr; Yubin Miao; Charles J. Smith (Molecules)
Effective molecular imaging and targeted cancer therapy rely on receptor-specific targeted delivery systems that are both metabolically stable and kinetically inert for optimal in vivo performance. Until now, no single metal complexing agent has demonstrated the versatility to coordinate metals across the periodic table while maintaining the kinetic inertness required for clinical theranostic applications. Therefore, enhancing the in vivo kinetic stability of radiolabeled, cell-targeting, biologically active compounds remains a critical goal to minimize unintended accumulation of radioactivity in collateral tissues. This review describes the usage of NOTA [NOTA = 1,4,7-triazacyclononane-1,4,7-triacetic acid] and derivatives of NOTA, a metal complexing agent that has been found to have the ability to effectively coordinate with a wide range of radiometals, including metal-radiohalogens, to form stable complexes. This enables the development of new cell-targeting small molecule and peptide conjugates with the potential to resist demetallation in vivo, thereby reducing radionuclide uptake in non-target tissues. Herein, we discuss the design and development of NOTA-based, cell-targeting, small molecules having very high affinity and selectivity for the GRPR (Gastrin-Releasing Peptide Receptor), the SSTR2 (Somatostatin Receptor Subtype 2), and the MC1R (Melanocortin-1) receptors that are present on the surfaces of numerous solid primary human tumors and their metastatic counterparts.